KEHADIRAN JENIS AMFIBI ORDO ANURA PADA AREAL REKLAMASI PASCA TAMBANG PT. KELIAN EQUATORIAL MINING KABUPATEN KUTAI BARAT - Mochamad Syoim (Fakultas Kehutanan Universitas Mulawarman, 2020)
PT Kelian Equatorial Mining (KEM) applied the open pit mining practice in its production phase in the past. The barred land was formed not only by the excavation and digging processes, but also formed by the dumping of the waste rocks. These processes were assumed as the factor the biodiversity decline or loss. The performance of completed and ongoing reclamation efforts, which refer to the most current regulation and law, is solely defined through the quantitative assessment on the survival of the planted tress on the reclamation site, on the other hand, despite very important, no such assessment is undertaken to examine the ecological recovery of the biodiversity on that site. Hence, this research aims at (1) identifying the presence of amphibians from the order of anura (frog and toad) in the reclamation sites of post open pit mining area, (2) identifying the dynamic of the presence of such amphibians during a 5 year time series. The research identified 13 species of amphibians, which categorized into 6 families. Most of the observed location are still dominated by the common species, which could be encountered in very common open area habitat.